1991
DOI: 10.1103/physreva.44.8421
|View full text |Cite
|
Sign up to set email alerts
|

Transition from a nonionic to an ionic micelle

Abstract: The present paper was motivated by an attempt to understand the transition from a nonionic to an ionic micelle from both the experimental and theoretical points of view. Small-angle neutron-scattering experiments were performed on mixed micelles of nonionic-ionic surfactants as the charge was increased in steps. Evidence for the charge condensation on the surface of the micelles is obtained. An extension of the sticky-hard-sphere model to include the Coulomb potentials is presented and used to analyze experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…As τ c (the value at which the stickiness parameter becomes sufficiently large to cause the micelles to flocculate) was approached, the system went directly from a single phase of micelles dominated by repulsive interactions to a flocculant. Using this approach, we were able to reproduce the results of earlier studies, 51,55,56 which predicted micelle growth at much higher volume fractions by aggregation of hard, sticky spheres and of charged, sticky spheres. Thus, we were not successful in using the Baxter approach to understand aggregation and growth in the conjugated bile saltfatty lipid systems at these relatively low concentrations.…”
Section: Discussionmentioning
confidence: 65%
“…As τ c (the value at which the stickiness parameter becomes sufficiently large to cause the micelles to flocculate) was approached, the system went directly from a single phase of micelles dominated by repulsive interactions to a flocculant. Using this approach, we were able to reproduce the results of earlier studies, 51,55,56 which predicted micelle growth at much higher volume fractions by aggregation of hard, sticky spheres and of charged, sticky spheres. Thus, we were not successful in using the Baxter approach to understand aggregation and growth in the conjugated bile saltfatty lipid systems at these relatively low concentrations.…”
Section: Discussionmentioning
confidence: 65%
“…Addition of Bu 4 N + , Bu 4 P + , or Am 4 N + to solutions of TX-100 increases the CP (Figure A), which may be due to the fact that the hydrophobic nature of these counterions would enable them to interact favorably with TX-100 micelles while a positive charge on them would introduce electrostatic repulsion between the micelles (due to adsorption at the micellar surface). CP increase has been observed in nonionic surfactant solutions on the addition of different organic acids/salts and also a few ionic surfactants. The increase in CP by quaternary ions is generally considered to be due to the more favorable interaction between water and the poly(ethylene oxide) (PEO) chains . It is further suggested that such salts affect the solvation capacity of water in relation to the PEO units, especially at higher temperatures .…”
Section: Resultsmentioning
confidence: 99%
“…CP increase has been observed in nonionic micellar solutions on the addition of different organic acids/salts and also a few ionic surfactants. [16][17][18][19][26][27][28][29][30] As shown by Valaulikar and Manohar, 19 addition of the latter to solutions of nonionic surfactants increased the CP by introducing electrostatic repulsion between the resultant mixed ionic micelles. They further demonstrated that the increase in CP could be described in terms of the surface charge per micelle.…”
Section: Resultsmentioning
confidence: 99%